How I prescribe prolonged intermittent renal replacement therapy - Clark, Edward G.; Vijayan, Anitha (Université d'Ottawa | University of Ottawa, 2023)
Abstract Prolonged Intermittent Renal Replacement Therapy (PIRRT) is the term used to define ‘hybrid’ forms of renal replacement therapy. PIRRT can be provided using an intermittent hemodialysis machine or a continuous renal replacement therapy (CRRT) machine. Treatments are provided for a longer duration than typical intermittent hemodialysis treatments (6–12 h vs. 3–4 h, respectively) but not 24 h per day as is done for continuous renal replacement therapy (CRRT). Usually, PIRRT treatments are provided 4 to 7 times per week. PIRRT is a cost-effective and flexible modality with which to safely provide RRT for critically ill patients. We present a brief review on the use of PIRRT in the ICU with a focus on how we prescribe it in that setting.